Species composition of birds colliding with noise barriers in białystok (north-eastern Poland) - Zbyryt, Adam; Suchowolec, Anna; Siuchno, Rafał (Zielona Góra: University of Zielona Góra, Faculty of Biological Sciences)
Until now in Poland there was no relevant data about the species composition of birds colliding with reflective plate glass in building construction and noise barriers. The research was conducted in 2010-2012. For the first two years the research was conducted only in breeding season, field control was carried out from 2 to 5 days. Since November 2011 an all year-long monitoring was started and the area was controlled once a week. In winter 2011/12 and spring 2012 there was conducted an experiment on time of carrion loss. In total there were 269 dead birds representing 43 species.
Keywords: species composition; noise barriers; collisions; Białystok; carrion